2021
DOI: 10.1098/rsos.210307
|View full text |Cite
|
Sign up to set email alerts
|

Outcome uncertainty influences probability perception and risk attitudes

Abstract: Subjective inferences of probability play a critical role in decision-making. How we learn about choice options, through description or experience, influences how we perceive their likelihoods, an effect known as the description–experience (DE) gap. Classically, the DE gap details how low probability described options are perceptually inflated as compared to equiprobable experience ones. However, these studies assessed probability perception relative to a ‘sure-bet’ option, and it remained unclear whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Thus, while information format did not itself drive the perceptual inflation of low probabilities, our results suggest that it does modulate probability perception. This is consistent with our prior study of the DE gap (Elston et al, 2021) that compared choice patterns across risky experience-based and description-based options and did not include a safe option. Our prior study indicated that subjective outcome likelihoods associated with experience-based options were perceptually inflated across all probabilities tested (20%, 50%, 80%).…”
Section: Information Format the Description-experience (De) Gap And T...supporting
confidence: 89%
See 4 more Smart Citations
“…Thus, while information format did not itself drive the perceptual inflation of low probabilities, our results suggest that it does modulate probability perception. This is consistent with our prior study of the DE gap (Elston et al, 2021) that compared choice patterns across risky experience-based and description-based options and did not include a safe option. Our prior study indicated that subjective outcome likelihoods associated with experience-based options were perceptually inflated across all probabilities tested (20%, 50%, 80%).…”
Section: Information Format the Description-experience (De) Gap And T...supporting
confidence: 89%
“…All candidate emojis were simple in color and form and did not contain faces or face-adjacent information (c.f. Elston et al, 2021). The probabilities of 20%, 50%, and 80% were randomly assigned to the emojis for each subject.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 3 more Smart Citations